The Dilemma of Multilateralism and the Adaptation and Transformation of International Environmental Law - Siyu Wu (Studies in Social Science & Humanities, 2025)
This article starts with the difficult problem of multilateralism and explores how multilateralism affects international environmental law in different ways, including the legal framework, implementation strategies and international cooperation. On this basis, the article explores how to rebuild multilateral cooperation, strengthen the rule of law, increase financial and technical assistance, and seek the help of non-state actors to adjust international environmental law. The conclusion of the article makes predictions on the conceptual changes of international environmental law, the integration of science and technology, and the development of multi-level governance models. In addition, the article also provides policy suggestions and theoretical support for global environmental governance.